Gazimağusa Devlet Hastanesi Servislerinde Yatan Diyabetli Hastaların Ayak Bakımına Yönelik Bilgi Düzeylerinin Belirlenmesi - Aydın, Mine (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The purpose of this research is to determine the level of foot care knowledge of patients with diabetes. The study was conducted in accordance with descriptive - cross sectional research design. The research was created by diabetic patients in Famagusta State Hospital. The sample of the study consisted of 250 adult diabetic patients who were able to understand and respond to research guidelines over the age of 18, lying within four months (16.02.2017-16.06.2017) within the internal medicine, between, surgery, neurology and services after the ethics committee’s permission was taken. As a data collection tool, Dr. Ayten Güner Atayoğlu's 'Diabetic Foot Care Survey Form' was used, taken from her expert's thesis with her permission. In the questionnaire form, there are a total of 40 questions about determining foot care information of patients with diabetes. The data were collected after receiving the ethical committe’s consent by admitting to the Famagusta State Hospital in the appropriate hours for the diabetic patients who had accepted the survey "Informed Consent Form” by interviewing the researcher face to face and conducting the "Diabetic Foot Care Survey Form." In the statistical analysis of the data, Chi-square test was used for the frequency analysis and frequency distribution. The statistical significance level is aeceptud to be ∞ = 0,05. According to the data obtained from the research; 53.2% of male patients; 34.0%, 56-65 years, 45.2% in the age group of 66 and above; more than half (67.6%), not literate and illiterate; 32.0% housewife; 31.6% of them are retired; 33.6% the duration of diabetes mellitus 6-10 years. 67% of patients did not participate in any diabetes education program and 33.2% had diabetic foot disease. The frequency of patients seeking a doctor for diabetes control; age, education, vi occupation, duration of diabetes, and diabetic education had a statistically significant difference. There is a statistically significant difference in the frequency of referral to a doctor for diabetic foot control; Those in "age group 55 and below"; "Middle and high school graduates"; "Civil servants and skilled workers' group; "Diabetes duration" has been determined to play a significant role for those who have been training for one month and five years with diabetes. It has also been determined that patients who graduated from seconday education and higher education have a higher rate of seeking information about diabetic foot and this makes a statistically significant difference. In the light of these results, the success of diabetes treatment and the prevention of complications, training of effective methods in accordance with the principles of adult education in the subjects of diabetes causes for patients and their relatives, treatment options, prevention of nutrition and exercise, self care, following blood glucose levels, compliance with treatment, avoidance of unexpected situations, recognition and prevention of complications, arrangement of courses are all advisable as well as suggesting nurses to update their knowledge and practice of diabetes on a continuing basis. Even though, some nurses are not diabetic nurses, but they may need to provide diabetes care for patients and their relatives, they need to train themselves first in the related field, so they can help and educate patients and their relatives. Nurses may be advised to update their knowledge and practice with regard to diabetes by receiving continuous training.

ÖZ: Bu araştırmanın amacı; diyabetli hastaların ayak bakımına yönelik bilgi düzeylerinin belirlenmesi olup tanımlayıcı – kesitsel araştırma tasarımına uygun olarak yapılmıştır. Araştırma evrenini, Gazimağusa Devlet Hastanesi’nde yatan diyabetli hastalar örneklemi ise, dâhiliye, cerrahi, nöroloji ve göğüs servislerinde, dört aylık süre içerisinde (16.02.2017 – 16.06.2017) yatan,18 yaş üstü, araştırma yönergelerini anlayabilme ve tepki verebilme yetisi olan erişkin 250 diyabetli hasta oluşturmuştur. Veri toplama aracı olarak Uzm. Dr. Ayten Güner Atayoğlu’nun uzmanlık tezinde kullandığı ve kullanım izni alınan ‘Diyabetik Ayak Bakımına Yönelik Anket Formu’ kullanılmıştır. Anket formunda, diyabetli hastaların ayak bakımına yönelik bilgilerini belirlemeye ilişkin toplam 40 soru yer almaktadır. Veriler; araştırmac tarafından görüşme yöntemi ile toplanmıştır. Verilerin istatiksel analizinde, frekans analizi ve frekans dağılımı Ki-kare testi kullanılmıştır. İstatiksel önemlilik düzeyi ∞=0,05 olarak kabul edilmiştir. Araştırmadan elde edilen bulgulara göre; hastaların, %53.2’si erkek; % 34.0’, 56-65 yaş, %45.2’si, 66 ve üstü yaş grubunda; yarıdan fazlasının (%67.6), okur-yazar ve okur-yazar değil; %32.0’si, ev hanımı; %31.6’sı, emekli; %33. 6’sının, diyabet hastalık süresi, 6-10 yıldır. Hastaların %67.2’si, diyabete ilişkin herhangi bir eğitim programına katılmamıştır ve %33.2’sinde, diyabetik ayak hastalığı bulunmaktadır. Hastaların diyabet kontrolü için doktora başvurma sıklığında; yaş, eğitim, meslek, diyabet süresi ve diyabete ilişkin eğitim alma durumunun, istatistiksel olarak anlamlı bir fark yarattığı saptanmıştır. Diyabetik ayak kontrolü için doktora başvurma sıklığında, istatistiksel olarak anlamlı fark yaratmada; “55 ve altındaki yaş grubunda” yer alanların; “orta ve yükseköğrenim mezunu” olanların; “memur ve vasıflı işçi grubundakilerin; “diyabet süresi” bir ay, beş yıl olanların ve diyabete ilişkin eğitim almış olanların rol oynadığı belirlenmiştir. Orta ve yükseköğrenim mezunu olan hastaların, diyabetik ayak konusunda bilgi almak isteme oranının, daha yüksek olduğu ve bu durumun da, istatistiksel olarak anlamlı fark yarattığı saptanmıştır. Bu sonuçlar doğrultusunda, diyabet tedavisinin başarısı ve komplikasyonların önlenmesi için, hasta ve yakınlarına; diyabet nedenleri, tedavisi, beslenmesi ve egzersizin önemli olduğu, öz bakımı ve kan glikoz düzeylerinin takibi, tedaviye uyumu, beklenmeyen durumlarla karşılaşıldığında nasıl başa çıkması konusunda, komplikasyonları tanıma ve önleme gibi konularda, erişkin eğitimi ilkeleri doğrultusunda etkin bir yöntemle eğitim verilmesi, kurslar düzenlenmesi, belirli aralarla kursların tekrarlanması, Bizim çalışmamızda olduğu gibi, hemşireler diyabet hemşiresi olmasalar da, hastanenin çeşitli servislerinde yatan diyabetli hastalara bakım vermek, hasta ve yakınlarını eğitmek durumunda olduklarından, hemşirelerin diyabet konusunda, sürekli eğitimlerle bilgi ve uygulamalarını güncellemeleri önerilebilir.
Hemşirelik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Hemşirelik Bölümü, 2018. Tez Danışmanı: Prof. Dr. Fethiye Erdil.
Keywords: Hemşirelik; Diyabet--Şeker Hastalığı; Diyabet; diyabetik ayak; bilgi gereksinimi; diyabet hemşiresi; Diabetes; diabetic foot; information requirement; diabetic nurses